Six Bacterial Vaginosis-Associated Species Can Form an In Vitro and Ex Vivo Polymicrobial Biofilm That Is Susceptible to Thymbra capitata Essential Oil - Rosca, Aliona S.; Castro, Joana; Sousa, Lúcia G. V.; França, Angela; Cavaleiro, Carlos; Salgueiro, Lígia; Cerca, Nuno (Frontiers in Cellular and Infection Microbiology, 2022)
Bacterial vaginosis (BV) is associated with serious gynaecologic and obstetric complications. The hallmark of BV is the presence of a polymicrobial biofilm on the vaginal epithelium, but BV aetiology is still a matter of debate. We have previously developed an in vitro biofilm model that included three BV-associated species, but, up to now, no studies are available whereby more bacterial species are grown together to better mimic the in vivo situation. Herein, we characterized the first polymicrobial BV biofilm consisting of six cultivable BV-associated species by using both in vitro and ex vivo vaginal tissue models. Both models revealed that the six species were able to incorporate the polymicrobial biofilm, at different bacterial concentrations. As it has been thought that this polymicrobial biofilm may increase the survival of BV-associated species when exposed to antibiotics, we also assessed if the Thymbra capitata essential oil (EO), which has recently been shown to be highly bactericidal against several Gardnerella species, could maintain its anti-biofilm activity against this polymicrobial biofilm. Under our experimental conditions, T. capitata EO exhibited a high antibacterial effect against polymicrobial biofilms, in both tested models, with a significant reduction in the biofilm biomass and the number of culturable cells. Overall, this study shows that six BV-associated species can grow together and form a biofilm both in vitro and when using an ex vivo model. Moreover, the data obtained herein should be considered in further applications of T. capitata EO as an antimicrobial agent fighting BV.